U kunt beginnen door te rationaliseren:
# (Sqrt (x + 1) + sqrt (1-x)) / (sqrt (1 + x) -sqrt (1-x)) x (sqrt (x + 1) + sqrt (1-x)) / (sqrt (x + 1) + sqrt (1-x)) = #
# = (Sqrt (x + 1) + sqrt (1-x)) ^ 2 / (2x) = #
# = ((1 + x) + 2sqrt (1 + x) sqrt (1-x) + (1-x)) / (2x) = #
# = (2 + 2sqrt (1-x ^ 2)) / (2x) = #
# = (1 + sqrt (1-x ^ 2)) / (x) = #
Het vervangen van: # X = sqrt (3) / 2 # Jij krijgt:
# = (1 + sqrt (1- 3/4)) / (sqrt (3) / 2) = (1 + 1/2) * (2 / sqrt (3)) = #
# = 3/2 * 2 / wortel (3) = 3 / sqrt (3) = 3 / sqrt (3) * sqrt (3) / sqrt (3) = sqrt (3) #
Ik hoop dat het is wat je nodig hebt!:-)